Cost-effectiveness of vaccination against HPV of adolescent girls in the regions of Russian Federation - A. V. Rudakova; S. M. Kharit; Yu. V. Lobzin (Журнал инфектологии, 2024)
Vaccination against human papillomavirus infection is not included in the National Calendar of Preventive Vaccinations of the Russian Federation, and vaccination is only available through regional programs. At the same time, the costeffectiveness of vaccination in the regions of the Russian Federation may vary significantly.The aim of this study was to assess the costeffectiveness of vaccination with the 4valent HPV vaccine in 12yearold girls in the regions of the Russian Federation.Materials and methods. A Markov model with a lifetime horizon for 12yearold girls based on epidemiological data for the Russian Federation was used. The costeffectiveness analysis was carried out from societal perspective. Costs and life expectancy were discounted at 3% per year.Results. In most regions of the Russian Federation, vaccination of girls is cost saving or highly costeffective (the cost per additional qualityadjusted life year (QALY) does not exceed the value of gross regional product per capita). Only in Dagestan, Chechnya and Ingushetia the vaccination of girls can be considered as costeffective, but not highly costeffective tool (incremental costs per QALY exceed the GRP per capita by 14,237,0%).Conclusions. Vaccination of girls before the onset of sexual activity with the 4valent HPV vaccine is highly costeffective in most regions of the Russian Federation.